Phenomenology of OCD: Lessons from a large multicenter study and implications for ICD-11 - Shavitt, Roseli G.; Mathis, Maria Alice de; Oki, Fabio; Ferrao, Ygor A.; Fontenelle, Leonardo F.; Torres, Albina Rodrigues [UNESP]; Diniz, Juliana B.; Costa, Daniel L. C.; Rosario, Maria Conceicao do; Hoexter, Marcelo Q.; Miguel, Euripedes C.; Simpson, H. Blair (Elsevier B.V., 2014)
This study aimed to investigate the phenomenology of obsessive compulsive disorder (OCD), addressing specific questions about the nature of obsessions and compulsions, and to contribute to the World Health Organization's (WHO) revision of OCD diagnostic guidelines. Data from 1001 patients from the Brazilian Research Consortium on Obsessive Compulsive Spectrum Disorders were used. Patients were evaluated by trained clinicians using validated instruments, including the Dimensional Yale Brown Obsessive Compulsive Scale, the University of Sao Paulo Sensory Phenomena Scale, and the Brown Assessment of Beliefs Scale. The aims were to compare the types of sensory phenomena (SP, subjective experiences that precede or accompany compulsions) in OCD patients with and without tic disorders and to determine the frequency of mental compulsions, the co-occurrence of obsessions and compulsions, and the range of insight. SP were common in the whole sample, but patients with tic disorders were more likely to have physical sensations and urges only. Mental compulsions occurred in the majority of OCD patients. It was extremely rare for OCD patients to have obsessions without compulsions. A wide range of insight into OCD beliefs was observed, with a small subset presenting no insight. The data generated from this large sample will help practicing clinicians appreciate the full range of OCD symptoms and confirm prior studies in smaller samples the degree to which insight varies. These findings also support specific revisions to the WHO's diagnostic guidelines for OCD, such as describing sensory phenomena, mental compulsions and level of insight, so that the world-wide recognition of this disabling disorder is increased. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Obsessive-compulsive disorder; Phenomenology; Sensory phenomena; Mental compulsions; Insight